2004
DOI: 10.1038/sj.bjc.6602028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of oesophageal cancer by detection of minichromosome maintenance 5 protein in gastric aspirates

Abstract: Symptomatic oesophageal cancer is usually advanced and the prognosis poor. Lethality of symptomatic oesophageal cancer has motivated screening for these diseases earlier in their evolution, but reliable methods for early diagnosis remain elusive. We have demonstrated that dysregulated expression of minichromosome maintenance (MCM) proteins 2 -7 is characteristic of early epithelial carcinogenesis, and that these key DNA replication initiation factors can be used as diagnostic markers for cervical and genito-ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 22 publications
3
43
1
Order By: Relevance
“…Notably, the arrested differentiation that characterizes cancer, particularly in high-grade tumours, is associated with failure to down-regulate the replication initiation proteins. (B) Spatial organization of Mcm2-7 protein expression in normal oesophageal squamous epithelium and non-dysplastic Barrett's mucosa and disruption of this highly organized spatial arrangement in premalignant dysplasia and invasive cancer [69,96]. In normal squamous epithelium, high expression levels of Mcm2 above a well-defined basal layer fall to undetectable levels in the upper third.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the arrested differentiation that characterizes cancer, particularly in high-grade tumours, is associated with failure to down-regulate the replication initiation proteins. (B) Spatial organization of Mcm2-7 protein expression in normal oesophageal squamous epithelium and non-dysplastic Barrett's mucosa and disruption of this highly organized spatial arrangement in premalignant dysplasia and invasive cancer [69,96]. In normal squamous epithelium, high expression levels of Mcm2 above a well-defined basal layer fall to undetectable levels in the upper third.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%
“…The detection of exfoliated MCM positive cells in body fluids (eg in urine, prostatic secretions, stool samples or gastro-oesophageal aspirates) or active sampling by swabbing or brushing (eg cervical smears or ERCP brushings for pancreaticobiliary tract sampling) provides a sensitive and specific method for the detection of premalignant and malignant lesions in a range of organ systems [39,[91][92][93][94][95][96][97][98]. For example, the immunostaining of cervical Pap smears for Mcm2-7 has potential to increase both the sensitivity and specificity of this error-prone test [39,[99][100][101].…”
Section: Gh Williams and K Stoebermentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the expansion of the proliferative compartment with increasing histological grade in preinvasive lesions is reflected by the appearance of MCM-positive abnormal cells at the surface of the epithelium. The dysregulated pattern of MCM expression has been detected in dysplasia and malignancy of cervical [14,15], laryngeal [16], colorectal [17,18], oesophageal [19][20][21], urothelial [22], and vulval [23] epithelia.…”
Section: Proteins As Diagnostic Prognostic and Predictive Tumoumentioning
confidence: 99%
“…We have also shown that dysregulation of MCM proteins is an early event in epithelial carcinogenesis, which occurs in a wide range of preneoplastic and neoplastic states resulting in exfoliation of MCM-positive tumour cells. Moreover, we have utilised these novel biomarkers of growth as diagnostic markers of cervical, genitourinary tract and oesophageal cancer (Williams et al, , 2004Stoeber et al, 1999Stoeber et al, , 2002.…”
mentioning
confidence: 99%